IMPLIKASI PMK NO 96 TAHUN 2023 TERHADAP BISNIS IMPOR DAN EKSPOR DI INDONESIA: Implications of PMK No 96 of 2023 on The Import and Export Business in Indonesia - Rais, Raifahd Razzaq (Fakultas Hukum, Universitas Trisakti, 2024)
PMK No. 96 of 2023 contains several important reform aspects which lie in adjusting regulations to the latest business practices, including the use of technology in customs and excise procedures, which promises process efficiency and greater transparency. Although PMK No. 96 of 2023 has positive objectives, implementation challenges include regulatory complexity and ambiguity which creates confusion and can hamper the import and export process. Seeing the complexity of PMK No. 96 of 2023 makes the author interested in analyzing the problem. What are the implications of PMK No. 96 of 2023 on Import and Export Business in Indonesia? and What are the challenges faced by export and import business actors in Indonesia in implementing the provisions of PMK No. 96 of 2023?, in this writing using normative juridical methods. This PMK stipulates policies that support and facilitate the delivery of e-catalogue and e-invoice data, speed up the customs clearance process, and increase transparency and efficiency by determining the responsibilities of each party involved.